Developing an App to Screen for Dual Disorders: A Tool for Improving Treatment Services in Mexico - Marín-Navarrete, Rodrigo; Torrens, Marta; Toledo-Fernández, Aldebarán; Mestre-Pinto, Joan Ignasi; Sánchez-Domínguez, Ricardo; Pérez-Lopez, Alejandro; Saracco-Alvarez, Ricardo; Madrigal-De León, Eduardo Ángel; Szerman, Nestor (Frontiers in Psychiatry, 2021)
Background: Previous studies in Mexico undertaken at residential facilities for treating substance use disorders (SUDs) reported that the prevalence of Dual Disorders (DDs) is over 65%. DDs represent a major challenge for the Mexican health system, particularly for community-based residential care facilities for SUDs, due to the lack of certified professionals to diagnose and treat these patients. Additionally, the absence of standardized algorithms for the screening and assessment of DDs to refer patients to specialized services (private or public) hinder timely care, delaying the start of integrated treatment. The use of new technologies provides a strategic opportunity through the development of digital and standardized applications for the timely detection of DDs. Objective: To develop an app for the screening of DDs, which will contribute to referral to specialized services according to the level of severity of psychiatric and addictive symptomatology, through the use of an app that will facilitate its application, portability and adoption in community-based residential care facilities for SUDs. Method: The research project was implemented in two stages. Stage 1: obtain the psychometric properties of the Dual Diagnosis Screening Interview (DDSI). Stage 2 consisted of two steps with the aim of testing the Beta version of the App and testing the quality of version 1.0. Results: The DDS obtained sensitivity and specificity scores upper to 85%. The app and its algorithm to screen and refer DDs proved to be efficient and easy to apply with satisfactory acceptance by the community. Conclusion: The development and dissemination of the app promises to be a useful screening tool at residential addiction treatment centers.